Educational Programme on Iron and Vitamin D Supplementation for Parents of Toddlers at Risk of Stunting - Amalia Cahya Agustina; Armelia Allya Sandika; Didik Nursetya Dewantoro; Prima Hapsari; Vidia Palupi; Warsinah (Pascasarjana Universitas Mataram, 2026)
Stunting is a chronic nutritional problem in toddlers that affects physical growth, cognitive development, and long-term health. One of the risk factors for stunting is iron and vitamin D deficiency, both of which play important roles in children’s growth and development. Educating parents about iron and vitamin D supplementation serves as a promotive and preventive strategy to reduce the risk of stunting, particularly among at-risk toddlers. This community service activity aimed to analyze the effect of parental education on the use of iron and vitamin D supplements among toddlers at risk of stunting. A pre-experimental design with a one-group pretest–posttest approach was employed. The participants were parents who received structured education on the benefits, dosage, and methods of administering iron and vitamin D supplements. The pretest results showed low knowledge in 22% of respondents, moderate in 22%, and high in 56%, while the posttest results indicated low knowledge in 5%, moderate in 10%, and high in 85%. Statistical analysis showed a significant increase in knowledge (p = 0.020), accompanied by improved practical understanding as observed from participants’ responses. This activity contributes to stunting prevention efforts by enhancing community-level micronutrient literacy.